(untitled) (Texas Journal of Engineering and Technology, 2022)
The principles, methods and algorithms are developed for control and correction of spelling mistakes in the electronic texts. Basic mechanisms are procedures of word-form chains association, allocation of correct morphemes and correction of monogram and combined mistakes. The developed algorithms are realized by parallel calculations technologies.